The Factorial Structure of Trait Anxiety and Its Mediating Effect Between Mindfulness and Depression - Wang, Tao; Li, Min; Xu, Song; Jiang, Chenggang; Gao, Dong; Wu, Tong; Lu, Fang; Liu, Botao; Wang, Jia (Frontiers in Psychiatry, 2018)
Background: It has been observed that high trait anxiety is a key susceptibility phenotype that causes depression. Mindfulness-based interventions can effectively target depressogenic vulnerability. Evidence indicates that trait anxiety could affect the trajectory of antidepressive psychotherapy and play an important role in the relationship between mindfulness and depression. Furthermore, related studies have suggested that trait anxiety could be a two-factor construct rather than a one-dimensional concept. This viewpoint provides a new perspective for exploring the pathways of the two factors of trait anxiety in the relationship between mindfulness and depression. Methods: A cross-sectional survey and a preliminary intervention study were conducted. A total of 1262 subjects completed a set of self-reported questionnaires that evaluated trait anxiety, mindfulness and depressive symptoms. Twenty-three eligible participants with depression were recruited to attend mindfulness-based cognitive training for eight weeks. The same questionnaires were administered one week before the training and six months after the training. Factor analysis was performed on the 1262-subject sample to explore and confirm the factorial structure of trait anxiety. In addition, mediating effect analysis was conducted in the two studies to test whether these two factors of trait anxiety were mediators of the relationship between mindfulness and depression. Results: The exploratory factor analysis extracted two dimensions of trait anxiety, namely, the trait anxiety-present factor (TA-P) and the trait anxiety-absent factor (TA-A). Confirmatory factor analysis showed that the fit of the two-factor model was acceptable. Both TA-P and TA-A were significantly negatively correlated with mindfulness and positively correlated with depression. The two factors of trait anxiety had multiple mediating effects on the relationship between mindfulness and depression, and the mediating effect of the TA-P was stronger than that of the TA-A. Conclusion: Our results demonstrated a two-factor model of trait anxiety in the Chinese population. TA-P and TA-A factors played multiple mediating roles in the relationship between mindfulness and depression. The findings provide new perspectives for psychological interventions to treat depression for people with susceptible personalities. Aiming to reduce negative emotional tendencies (TA-P) and enhance positive cognition (TA-A) may achieve the early prevention and efficient treatment of depression.